High IF digitizer based on quantized feedback - Namdar Mehdiabadi, Ardeshir. (University of Waterloo, 1998)
This thesis discusses the issues and solutions of quantized feedback for high IF digitizers in wireless communication systems. The first part of the thesis examines different types of architectures that can be used for IF digitizers. In the second part of the thesis. the quantized feedback and its effect on the distortion is examined and compared with the continuous amplitude feedback method. A new sigmadelta modulator architecture is proposed to improve quantized feedback behavior and a brief theoretical analysis is mentioned. Design problems due to the new architecture are investigated and a 400MHz IF digitizer with low distortion using the new technique is designed. The prototype design achieves a very low distortion and suppresses the loop distortion created by conventional architectures by more than 40dB. The IM3 for this prototype is also reduced by more than 20dB.
Keywords: Harvested from Collections Canada